2020
DOI: 10.1038/s41427-019-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional electrochromic energy storage devices by chemical cross-linking: impact of a WO3·H2O nanoparticle-embedded chitosan thin film on amorphous WO3 films

Abstract: With the advent of multifunctional devices with electrochromic (EC) behavior and electrochemical energy storage, complementary design of film structures using inorganic-organic materials has shown great potential for developing EC energy storage devices. Herein, hybrid films consisting of WO 3 ·H 2 O nanoparticle (WHNP)-embedded chitosan thin films on amorphous WO 3 (a-WO 3 ) films were designed. By exploiting the hybrid effect of chitosan and WHNPs to generate unique chemical cross-linking between them, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…1d, the binding energy peaks at 35.48 and 37.58 eV belong to W 4f 7/2 and W 4f 5/2 , representing W 6+ , while an additional binding energy peak at 41.31 eV was attributed to W 5p 3/2 of the WO 3 NSHs, indicating the chemical value of W was +6. [28][29][30] Furthermore, the O 1s binding energy peak (Fig. 1e) could be resolved into two dominant components at 530.31 and 531.61 eV, corresponding to the lattice oxygen ion and the surfaceabsorbed oxygen species.…”
Section: Resultsmentioning
confidence: 96%
“…1d, the binding energy peaks at 35.48 and 37.58 eV belong to W 4f 7/2 and W 4f 5/2 , representing W 6+ , while an additional binding energy peak at 41.31 eV was attributed to W 5p 3/2 of the WO 3 NSHs, indicating the chemical value of W was +6. [28][29][30] Furthermore, the O 1s binding energy peak (Fig. 1e) could be resolved into two dominant components at 530.31 and 531.61 eV, corresponding to the lattice oxygen ion and the surfaceabsorbed oxygen species.…”
Section: Resultsmentioning
confidence: 96%
“…One key parameter for achieving high-performance ECSs is an EC chromophore. Among EC materials, transition metal oxides such as tungsten trioxide (WO 3 ) have been widely employed to exploit their superior electrochemical properties [16][17][18] , large optical modulation 19,20 , and high coloration efficiency 21,22 . Recently, a few research groups reported ECSs based on WO 3 films [23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Starting with the fundamental electrochemical reaction, electrochromic performances of the WO 3− x depend on the transport rate of the cations and electrons as well as the ability to accommodate the cations in the film. Different advanced strategies have been studied to improve electrochromic performances such as the combination of crystalline and amorphous WO 3− x [ 20 , 21 ], regulation of nanotopography [ 6 , 22 , 23 ], element doping [ 18 , 24 , 25 ], and construction of composite materials [ 26 , 27 ]. On the one hand, the structure construction of tungsten oxide almost concentrates on the transport behavior of cations.…”
Section: Introductionmentioning
confidence: 99%